2018
DOI: 10.1111/jcpe.12931
|View full text |Cite
|
Sign up to set email alerts
|

Human intrabony defect regeneration with micrografts containing dental pulp stem cells: A randomized controlled clinical trial

Abstract: Application of DPSCs significantly improved clinical parameters of periodontal regeneration 1 year after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
172
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(181 citation statements)
references
References 53 publications
1
172
1
7
Order By: Relevance
“…Only one study provided data for plaque index with the full‐mouth plaque score. The MD between test and control groups was −1.60% (95% CI [−4.23; 1.03]).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study provided data for plaque index with the full‐mouth plaque score. The MD between test and control groups was −1.60% (95% CI [−4.23; 1.03]).…”
Section: Resultsmentioning
confidence: 99%
“…After assessment of the full papers, a further 56 records were excluded. Therefore, a total of 18 publications corresponding to 16 original studies were included for qualitative analysis. One of the included studies reported follow‐up data from a previously published study , whereas another one was a correction of a previous report .…”
Section: Resultsmentioning
confidence: 99%
“…There was a total of 11 randomized controlled trials (RCTs) and 5 non‐randomized controlled original trials included for qualitative analysis. All RCTs incorporated a parallel design, whereas CCTs included reports with either a parallel or a “split mouth” design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations